Analisis Pengaruh Kecerdasan Emosional, Stres Kerja dan Kepuasan Kerja terhadap Komitmen Organisasional (Studi pada Perawat Unit Rawat Inap RS Panti Waluya Malang) - Karambut, Christien A (Jurnal Aplikasi Manajemen, 2012)
The research aims to analyze the influence of emotional intelligence, work stress and job satisfactionon organizational commitment, both directly and indirectly. This research is done on nurses who workin care unit of Panti Waluya Hospital Malang, amounted at 124 people spread in nine caring rooms.Technique used in sampling is census, where all of the population is used as sample. Analysis unit used ispath analysis. The research result that emotional intelligence and job satisfaction influence positively andsignificantly on organizational commitment, while work stress influence negatively and significantly onorganizational commitment. Other than that emotional intelligence and work stress influence indirect onorganizational commitment through job satisfaction.